Peran Sistem Informasi Manajemen (SIM) Dalam Peningkatan Kualitas Pelayanan Publik di Kantor Camat Sakra Timur: The Role of Management Information Systems (MIS) in Improving the Quality of Public Services at the East Sakra District Office - Masbullah Masbullah (Engineering and Technology International Journal, 2021)
The purpose of this study was to determine the role of information system management in improving the quality of public services at the Sakra Timur sub-district office. The research method used in this research is descriptive qualitative, namely research that describes and aims to provide an overview and explanation of the variables carried out according to the research focus including the role of information systems in managing information, generating information and presenting information as well as inhibiting factors and supporters in improving the quality of public services at the Sakra Timur sub-district office. This study used purposive sampling and accidental sampling, then data collection techniques were carried out by conducting in-depth interviews and document research. The results of the study can be said that the management information system plays a very important role in managing information, generating information, and presenting information. By using computer systems and other technological devices, information can be managed and conveyed to what is needed quickly and accurately, as well as making it easier for employees at the Sakra Timur District Office to complete their respective tasks and work, especially those related to public services. . This is inseparable from the inhibiting and supporting factors, while those that support the improvement of service quality at the Sakra Timur District Office are information and communication technology. And the obstacles are the slow network, power outages, lack of ability of the employees of the East Sakra District to use or operate technology such as computers and devices, however, the East Sakra District Office has made every effort to improve services to the community.